Analisis Pengaruh Locus Of Control, Goal Orientation Dan Kompleksitas Tugas Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening (Studi Kantor Pelayanan Pajak Pratama Surakarta) - Triyani, Triyani; , Drs. Wiyadi, M.M, Ph.D; , Drs. M. Farid Wajdi, M.M,Ph.D (2017)
The aim of this research to examine and analyze the impact of locus of control, goal orientation and complexity of tasks to employees performance and job satisfaction as an intervening variable. This is an explanatory research with quantitative approach. The scope of the research is identified as all the employees at KPP Pratama Surakarta. The collection of data and information needed in the research conducted by field research. The data used are primary data obtained directly from the subject of research in the form of respondents' perception by a questionnaire to 110 respondents. The research shows variable locus of control significantly influence employees performance and negative not significant influence job satisfaction. Goal orientation has negative and not significant influence employees performance and positive significant influence job satisfaction. Complexity of the task has positive significant influence toward employees performance and employee's job satisfaction. Job satisfaction has negative and also not able to be variable intervening between the performance of the independent variable.